2018
DOI: 10.4103/ijph.ijph_77_17
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of congenital anomalies in a rural population of Jammu - A prospective study

Abstract: The study demonstrated that the CAs continue to occur in Jammu at a similar magnitude as reported from other parts of the country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…But differences still exist in various geographic areas. Gastro-intestinal system anomalies were the commonest (35%) followed by CNS (26.6%) in a study conducted in Jammu [9]. Cardiac anomalies were the commonest among newborn live births in a study reported from central India [10].However, Sarkar et al reported that musculoskeletal anomalies were commonest in their study in Eastern India [11].…”
Section: Discussionmentioning
confidence: 92%
“…But differences still exist in various geographic areas. Gastro-intestinal system anomalies were the commonest (35%) followed by CNS (26.6%) in a study conducted in Jammu [9]. Cardiac anomalies were the commonest among newborn live births in a study reported from central India [10].However, Sarkar et al reported that musculoskeletal anomalies were commonest in their study in Eastern India [11].…”
Section: Discussionmentioning
confidence: 92%
“…Since past few years, a number of suspected cases of genetic disorders (including new/known monogenic diseases and other known genetic diseases with atypical clinical features) have been reported from J&K region. Cases of chromosomal genetic disorders (such as Down Syndrome, Turner Syndrome, Klinefelter Syndrome, Patau Syndrome; Table 5), anemias, blood disorders (including Thalassemia), congenital anomalies, disorders of sex development, metabolic disorders like G6PD deficiency, neurological disorders (Table 6) and others are frequently reported in J&K (Razdan et al, 1994;Kumar et al, 2010;Upma et al, 2010;Vasudev and Sawhney, 2014;Ara et al, 2018;Dar et al, 2018;Hockham et al, 2018). The detrimental effects of consanguinity and inbreeding depression on child health and mortality, cognitive behavior and fertility and an increased risk of cardiovascular diseases in small population groups from J&K has also been reported (Bhasin and Nag, 2002b;Afzal, 2014a,b, 2016;.…”
Section: Burden Of Genetic Diseases In Jandkmentioning
confidence: 99%
“…[1][2][3] The global estimated prevalence of Congenital anomalies is between 1% and 3% and varies widely among countries. 2,5,6 Congenital anomalies affect 1 in every 33 newborns. 4 Birth prevalence of congenital anomalies is affected due to social, racial, economical, and ecological influences.…”
mentioning
confidence: 99%
“…The cause of congenital anomalies is considered multifactorial, which accounts for two-thirds of all defects. 1,5 Risk factors attributed to their development include metabolic factors, such as hypothyroidism, uncontrolled diabetes, and maternal obesity. 3,5 Maternal exposures to certain drugs (trimethoprim, phenytoin, phenobarbitone and carbamazepine), infections (TORCHs-toxoplasmosis, others (syphilis, hepatitis B), rubella, cytomegalovirus (CMV) and herpes simplex) and radiation have been implicated.…”
mentioning
confidence: 99%
See 1 more Smart Citation